Subduction-accretion complex with boninitic ophiolite slices and Triassic limestone seamounts: Ankara Mélange, central Anatolia - Okay, Aral; Altıner, Demir; Danelian, Taniel; Topuz, Gültekin; Özcan, Ercan; Kylander-Clark, Andrew Rc (Cambridge University Press (CUP), 2022)
AbstractOphiolitic mélanges in Anatolia represent Mesozoic subduction-accretion complexes, which are unusually poor in land-derived coarse-clastic rocks. A segment of the ophiolitic mélange in the Beynam region south of Ankara was studied. The ophiolitic mélange consists of three accretionary units (AUs), which are distinguished by lithology, structure, age and geochemistry. At the base there is a serpentinite mélange, which is overlain by a semi-intact Upper Jurassic ophiolite with boninite geochemistry. The topmost AU consists of ocean-island-like alkali basalts with seamount-derived Triassic shallow-marine limestones and Jurassic radiolarian cherts, which are stratigraphically overlain by Upper Cretaceous fore-arc turbidites. The base of the fore-arc sequence is palaeontologically and isotopically dated to the early to middle Campanian (c. 81 Ma). Detrital zircons from the fore-arc sequence indicate a Late Cretaceous (87–81 Ma) magmatic arc as a source. The formation of the subduction-accretion complex was a two-stage process. The first stage took place during the Late Jurassic – Early Cretaceous, when supra-subduction type oceanic crust was generated, and subduction accretion was intra-oceanic. In the second stage during the Late Cretaceous the subduction jumped inboard, creating an Andean-type convergent margin, and the Jurassic oceanic crust was incorporated in the subduction-accretion complex. The lack of land-derived sandstones in the ophiolitic mélange can be attributed to the intra-oceanic subduction and to the limestone deposition in the upper plate during the main phase of subduction accretion in the Late Jurassic – Early Cretaceous.
Keywords: [SDU] Sciences of the Universe [physics]